2022
DOI: 10.1186/s40902-022-00364-4
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of digital surgical guides for dental implants

Abstract: Background Recently developed imaging techniques, such as cone beam computed tomography (CBCT) and CAD/CAM technology, have facilitated reliable implant planning and implant surgical guide production by 3D printing. This study compared the accuracy of implant-guided surgery using the R2GATE® program with CBCT before and after surgery. Patients and methods The study included patients who visited the Department of Oral and Maxillofacial Surgery at Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…A template-guided implant placement study revealed that implant insertion with a length of 8 to 9 mm resulted in significantly higher precision than insertion with lengths of 10 to 11 mm and 12 to 13 mm, although angle deviation was unaffected by implant length [ 25 ]. Similarly, a recent research has shown that there is a statistically significant difference in the deviation of the apical and cervical regions during implant placement, depending on the implant diameter and length, when using digital surgical guides for dental implants [ 26 ]. In order to reduce the influence of this aspect, we utilized the same implant diameter and length for each paired group.…”
Section: Discussionmentioning
confidence: 99%
“…A template-guided implant placement study revealed that implant insertion with a length of 8 to 9 mm resulted in significantly higher precision than insertion with lengths of 10 to 11 mm and 12 to 13 mm, although angle deviation was unaffected by implant length [ 25 ]. Similarly, a recent research has shown that there is a statistically significant difference in the deviation of the apical and cervical regions during implant placement, depending on the implant diameter and length, when using digital surgical guides for dental implants [ 26 ]. In order to reduce the influence of this aspect, we utilized the same implant diameter and length for each paired group.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the angular deviation between the planned and placed implants exhibited a variance of 3.42 ± 2.12°. 16 In evaluating factors influencing implant placement accuracy, statistically significant differences were observed in cases involving tissue-supported implant guide, implant diameter, and implant length. 48 Similarly, dynamic computer-aidedd implant surgery achieves an accuracy within a clinically acceptable range and exhibits potential for clinical implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these technologies have enabled the production of implant surgical guides through 3D printing, thereby enhancing the overall efficacy of dental implant procedures. 16 Augmented reality (AR) has progressively been applied in dental implant surgery, marking another dimension of technological integration. Nevertheless, the level of improvement in accuracy that can be achieved by integrating a dynamic navigation system with AR technology is currently unknown and requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the patient's history of gastroesophageal acid reflux [11] and existing dental implants, the nearby prosthesis made of "all metals" could potentially lead to galvanism [13]. As highlighted by Kim SM (2023), contact between two different metal alloys in the presence of saliva initiates electrochemical reactions [13]. This phenomenon can result in galvanic erosion, additional soft tissue problems, tooth erosion, crown corrosion, and peri-implantitis [13].…”
Section: Introductionmentioning
confidence: 99%
“…As highlighted by Kim SM (2023), contact between two different metal alloys in the presence of saliva initiates electrochemical reactions [13]. This phenomenon can result in galvanic erosion, additional soft tissue problems, tooth erosion, crown corrosion, and peri-implantitis [13]. Therefore, in light of the patient's color preference, concerns regarding GERD, and the risk of galvanism, a monoblock post-fused porcelain crown was selected for this case.…”
Section: Introductionmentioning
confidence: 99%